2010
DOI: 10.1007/s00203-010-0633-1
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Vibrio cholerae biofilm by AiiA enzyme produced from Bacillus spp.

Abstract: Vibrio cholerae is the causative agent of water-borne diarrheal disease, cholera. The formation of biofilm favors survival and persistence of V. cholerae in the aquatic environment and also inside the host. AHL lactonase (AiiA), a metallo-beta-lactamase produced by Bacillus spp., blocks quorum sensing in Gram-negative bacteria by hydrolyzing N-acyl-homoserine lactones (AHLs). In the present investigation, AiiA-mediated inhibition of V. cholerae biofilm was studied. Two novel alleles of aiiA-encoding genes from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(36 citation statements)
references
References 18 publications
0
36
0
Order By: Relevance
“…4) (85), demonstrating for the first time the potential of quorum quenching in disease prevention. Following these initial reports, aiiA genes were identified in various other Bacillus species (56,60,(87)(88)(89), and heterologous expression of various aiiA alleles in numerous pathogenic bacteria, including P. aeruginosa and Burkholderia thailandensis, reduced AHL accumulation and altered QS-dependent behaviors (60,90). Additional studies have since provided further evidence of the utility of enzymatic quorum quenching for disease prevention and treatment in a variety of plant models using both transgenic plant species (91,92) and wild-type (WT) and engineered AiiA-expressing bacteria (88,89,(93)(94)(95)(96).…”
Section: Enzymatic Degradation and Inactivation Of Ahlsmentioning
confidence: 99%
“…4) (85), demonstrating for the first time the potential of quorum quenching in disease prevention. Following these initial reports, aiiA genes were identified in various other Bacillus species (56,60,(87)(88)(89), and heterologous expression of various aiiA alleles in numerous pathogenic bacteria, including P. aeruginosa and Burkholderia thailandensis, reduced AHL accumulation and altered QS-dependent behaviors (60,90). Additional studies have since provided further evidence of the utility of enzymatic quorum quenching for disease prevention and treatment in a variety of plant models using both transgenic plant species (91,92) and wild-type (WT) and engineered AiiA-expressing bacteria (88,89,(93)(94)(95)(96).…”
Section: Enzymatic Degradation and Inactivation Of Ahlsmentioning
confidence: 99%
“…In the unicellular alga Chlamydomonas reinhardtii, expression of the codon-optimised AiiA altered the composition of the alga-associated microbiota (Rajamani et al 2011). When AiiA was expressed in V. cholera, it completely eradicated biofilm formation (Augustine et al 2010). Transgenic aiiA-expressing bacteria have also been used to disrupt industrial biofilms: the introduction of micro-encapsulated transgenic E. coli strongly reduced biofouling of membranes in wastewater treatment facilities over an extended period of time (Oh et al 2012).…”
Section: Enzymes That Degrade Biofilm-forming Qs Signalsmentioning
confidence: 99%
“…Impairing bacterial communication systems such as the quorum sensing can affect bacterial ability to form biofilm, as in the case of Bacillus cereus production of an AHL lactonase inhibiting Vibrio cholerae biofilm settlement [13]. Cugini et al (2007) also reported that C. albicans produces farnesol, a quorum sensing molecule, that inhibits the swarming mobility of P. aeruginosa , thereby enhancing its ability to form biofilm [14], [15].…”
Section: Introductionmentioning
confidence: 99%